2020
DOI: 10.1371/journal.pone.0233525
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the suitability of six drought indices in naturally growing, transitional vegetation zones in Inner Mongolia (China)

Abstract: Naturally growing vegetation often suffers from the effects of drought. There exists a vast number of drought indices (DI's) to assess the impact of drought on the growth of crops and naturally occurring vegetation. However, assessing the fitness of these indices for large areas with variable vegetation cover is often problematic because of the absence of adequate spatial information. In this study, we compared six DI's to NDVI (the normalized difference vegetation index), a common indicator of vegetation occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 43 publications
0
23
0
1
Order By: Relevance
“…We selected four grassland types in the Inner Mongolia (112°21'-118°22′E, 43°25′-47°33′N), an autonomous region of China, which includes meadow steppe, typical steppe, steppe desert, and desert steppe. Recent studies have demonstrated that these grasslands are of great threat of climatic variability (John et al, 2018;Wang et al, 2020) (John et al, 2016(John et al, , 2018Wang et al, 2020). Vegetation in meadow steppe and typical steppe are herbaceous in nature and shallow rooted species that are less tolerant to increasing climatic variability (John et al, 2018), while vegetation in steppe desert and desert steppe are deep rooted species that can absorb shocks resulted from disturbance (e.g., low precipitation in growing-season) (Wang et al, 2020).…”
Section: Description Of Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…We selected four grassland types in the Inner Mongolia (112°21'-118°22′E, 43°25′-47°33′N), an autonomous region of China, which includes meadow steppe, typical steppe, steppe desert, and desert steppe. Recent studies have demonstrated that these grasslands are of great threat of climatic variability (John et al, 2018;Wang et al, 2020) (John et al, 2016(John et al, , 2018Wang et al, 2020). Vegetation in meadow steppe and typical steppe are herbaceous in nature and shallow rooted species that are less tolerant to increasing climatic variability (John et al, 2018), while vegetation in steppe desert and desert steppe are deep rooted species that can absorb shocks resulted from disturbance (e.g., low precipitation in growing-season) (Wang et al, 2020).…”
Section: Description Of Study Areamentioning
confidence: 99%
“…Recent studies have demonstrated that these grasslands are of great threat of climatic variability (John et al, 2018;Wang et al, 2020) (John et al, 2016(John et al, , 2018Wang et al, 2020). Vegetation in meadow steppe and typical steppe are herbaceous in nature and shallow rooted species that are less tolerant to increasing climatic variability (John et al, 2018), while vegetation in steppe desert and desert steppe are deep rooted species that can absorb shocks resulted from disturbance (e.g., low precipitation in growing-season) (Wang et al, 2020). Mean annual temperature is −2.2°C in meadow steppe, 3.0°C in typical steppe, 5.1°C in steppe desert, and 7.2°C in desert steppe (Wang et al, 2020).…”
Section: Description Of Study Areamentioning
confidence: 99%
“…Studying the change in aridity at the regional scale helps to understand the magnitude, identify the extreme hot spot areas and spatial pattern of the changes as well as the shift of lands from one class of aridity to another arid class. The transition of aridity is considered as a foremost and assertive impact of global climate change [27,43,44] . The study examines the sensitivity of gridded precipitation data sets for identification of semi-arid regions over India.…”
Section: Discussionmentioning
confidence: 99%
“…The Moderate Resolution Imaging Spectro-radiometer (MODIS) provides these vegetation indices fortnightly that are useful in anomaly studies. The NDVI anomaly can be studied along with meteorological indices (AIA and SPI) to characterize drought related impacts on growing vegetation at timescales from month to year [24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…The SPI method is one of the 150 methods developed as drought indices. Apart from the SPI, the other common methods used in drought studies are the Standardized Precipitation Evapotranspiration Index (SPEI), the Palmer Drought Severity Index (PDSI), and the Precipitation Anomaly Percentage ( Wang et al, 2020 ). The SPEI is the index used to take into account the drought damage based on the climate balance between precipitation and evapotranspiration.…”
Section: Introductionmentioning
confidence: 99%